Pengaruh Kecerdasan Spiritual, Kecerdasan Emosi, Sikap Budaya Organisasi, dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior pada Guru Sekolah Menengah Kejuruan Negeri Kelompok Teknologi dan Industri di Kabupaten Tegal - Heny Indriani; Inayah Adi Sari (Universitas Peradaban, 2017)
This research is motivated by a variety of problems associated with Organizational Citizenship Behavior (OCB) that exist on teacher of Public Vocational High School (SMK Negeri) at Technology and Industry Group in Tegal. This study aimed to analyze the causal relationship between the model of spiritual intelligence, emotional intelligence, attitudes on organizational culture and commitment to the Organizational Citizenship Behaviour ( OCB ) as teacher at SMK Negeri Technology and Industry Group in Tegal regency. The population in this study was a teacher at SMK Group Technology and Industry in Tegal. The method used is quantitative methods, namely multiple linear regression analysis. The results showed the existence of a causal relationship between spiritual intelligence, emotional intelligence, organizational culture and attitudes in the organization's commitment to the OCB, it known from the value of F statistic of 761.450 with a significant probability value 0,000 far below 0.05 so it can be said that the hypothesis stating there is the influence of spiritual intelligence, emotional intelligence, attitudes on organizational culture, and organizational commitment, together on Organizational Citizenship Behavior is accepted as true. Based on these results, it is to improve the OCB teachers SMK Group Technology and Industry in Tegal need to be implemented seminars, workshops, and training ESQ (Emotional and Spiritual Quotient), reward and punishment in improving organizational commitment and attitudes on organizational culture, as well as a good example of the principal as leader of the organization.